The Question in the Bottle (Homoeopathy for All, 2026)
There is a moment every  homoeopathic physician knows. The patient is sitting before us. The  case has been taken with care. The  symptoms have been weighed, the  modalities examined, the mental  and physical generals understood,  and the totality has slowly begun to  point toward a remedy. After much  thought, the prescription is written  Then, almost silently, another  question rises. Which company’s medicine should  I give? Is this Sulphur 30 truly comparable  with another Sulphur 30? Is this  Natrum muriaticum 200 from one  pharmacy the same in quality,  preparation, and reliability as  the same medicine from another  manufacturer? When I place a small  bottle in the hands of my patient, am  I only relying on my knowledge of  materia medica, or am I also silently  trusting a chain of pharmaceutical  processes that I cannot fully see? This question has lived with  me since 1990, when I began my  practice. It has followed me through  thousands of prescriptions, countless  follow-ups, and many moments of  clinical uncertainty. It became even  sharper when I taught homoeopathic  pharmacy to undergraduate students  at Bakson Homoeopathic Medical  College. I was not only teaching  them the technical preparation of  medicines. I was preparing them for  the realities of practice.
Keywords: homoeopathic; physician; sitting; symptoms; weighed